Directing Differentiation of Pluripotent Stem Cells Toward Retinal Pigment Epithelium Lineage. (24th August 2016) - Choudhary, Parul; Booth, Heather; Gutteridge, Alex; Surmacz, Beata; Louca, Irene; Steer, Juliette; Kerby, Julie; Whiting, Paul John
Abstract: Development of efficient and reproducible conditions for directed differentiation of pluripotent stem cells into specific cell types is important not only to understand early human development but also to enable more practical applications, such as in vitro disease modeling, drug discovery, and cell therapies. The differentiation of stem cells to retinal pigment epithelium (RPE) in particular holds promise as a source of cells for therapeutic replacement in age-related macular degeneration. Here we show development of an efficient method for deriving homogeneous RPE populations in a period of 45 days using an adherent, monolayer system and defined xeno-free media and matrices. The method utilizes sequential inhibition and activation of the Activin and bone morphogenetic protein signaling pathways and can be applied to both human embryonic stem cells and induced pluripotent stem cells as the starting population. In addition, we use whole genome transcript analysis to characterize cells at different stages of differentiation that provides further understanding of the developmental dynamics and fate specification of RPE. We show that with the described method, RPE develop through stages consistent with their formation during embryonic development. This characterization— together with the absence of steps involving embryoid bodies, three-dimensional culture, or manual dissections, which are common features of other protocols—makes this process very attractive for use in research as well as for clinical applications.